1997
DOI: 10.1007/bf01301434
|View full text |Cite
|
Sign up to set email alerts
|

Temporary external fixation for low back pain: Is it worth doing?

Abstract: Thirty-three patients with low back pain underwent spinal fusion following a positively predicting external fixation test. Thirty-two spinal fusions and one sacroiliac joint fusion were performed. The complications following the use of the external fixator were significant. The results following spinal fusion were not related to the positive response to the external fixator. Multiple variables affect the results of spinal fusion. We feel that the external fixator test in low back pain management is very invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Other authors reported an infection rate of 2% up to 18%. 17,18,[22][23][24][25] Probably, complication rate increases with the duration of the test. 23 Since May 1997, flucloxacillin was administered orally in this trial as long as the external fixator was in situ.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other authors reported an infection rate of 2% up to 18%. 17,18,[22][23][24][25] Probably, complication rate increases with the duration of the test. 23 Since May 1997, flucloxacillin was administered orally in this trial as long as the external fixator was in situ.…”
Section: Discussionmentioning
confidence: 98%
“…The 8% nerve root irritation in the current study is in concordance with the 0% to 9% reported in other series of external skeletal fixations. 17,18,[22][23][24][25] In 2 patients, the external fixator had to be removed before completion of the test due to pain caused by root irritation. No permanent neurologic deficit was found.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in vitro studies have shown that under axial compressive loads the ESF still allows substantial axial translation [10,20], and does not reduce the loads acting on the disc [4]. Edwards et al concluded that the ESF relieves pain by reducing flexion and inhibiting the bulging of the disc [4], but other factors than purely mechanical ones have also been suggested [6,13].…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional stabilization provided by the external spinal fixator compared to two internal fixation devices: a biomechanical in vitro flexibility study basis of this pain relief is still unknown, but additional mechanisms other than stabilization of the suspected painful segments have been suggested [6,13].…”
Section: Teija Lund Thomas Nydeggermentioning
confidence: 99%
See 1 more Smart Citation